2017
DOI: 10.3389/fnhum.2017.00610
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Recruitment of Frontoparietal and Salience Networks for Voluntary Decisions

Abstract: There is evidence that neural patterns are predictive of voluntary decisions, but findings come from paradigms that have typically required participants to make arbitrary choices decisions in highly abstract experimental tasks. It remains to be seen whether proactive neural activity reflects upcoming choices for individuals performing decisions in more complex, dynamic, scenarios. In this functional Magnetic Resonance Imaging (fMRI) study, we investigated proactive neural activity for voluntary decisions compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…The frontoparietal control network (FPCN) is an attention control network, also known as the central executive network or the frontoparietal central executive network (Menon, 2011). It encompasses the dorsolateral and anterior prefrontal cortices, inferior parietal lobes, AI, and ACC (Vincent et al, 2008;Rens et al, 2017). Notably, the latter two regions (AI and ACC) overlap with the SN.…”
Section: P Connectivity Within Large-scale Resting-state Networkmentioning
confidence: 99%
“…The frontoparietal control network (FPCN) is an attention control network, also known as the central executive network or the frontoparietal central executive network (Menon, 2011). It encompasses the dorsolateral and anterior prefrontal cortices, inferior parietal lobes, AI, and ACC (Vincent et al, 2008;Rens et al, 2017). Notably, the latter two regions (AI and ACC) overlap with the SN.…”
Section: P Connectivity Within Large-scale Resting-state Networkmentioning
confidence: 99%
“…Underscoring the importance of this confound, there is clear evidence that decisions can drive decoding, although these studies do not explicitly investigate the role of attention. For instance, decisions can be decoded from early visual areas (Löffler et al, 2019; Rens et al, 2017), as well as from frontoparietal cortex (Löffler et al, 2019). In these paradigms, the decision was not driven by visual information, as participants had to make a choice between multiple options.…”
Section: Introductionmentioning
confidence: 99%
“…The brain-mind can interpret it unconsciously if its facial features and body language inspire confidence or danger [46]. Also, neuroscience on anticipatory unconscious processing [43], [44], [45], [62], [63] has found neural activity corresponding to the upcoming choice. As Soon et al reported [64], [65] a decision can be encoded in the brain activity of the prefrontal and parietal cortex up to 10 s before it enters awareness.…”
Section: Discussionmentioning
confidence: 99%